Mean Reversion in Stock Prices: Implications for Long-Term Investors - Laura Spierdijk; Jacob A. Bikker (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2012)
This paper discusses the implications of mean reversion in stock prices for longterm investors such as pension funds. We start with a general definition of a meanreverting price process and explain how mean reversion in stock prices is related to mean reversion in stock returns. Subsequently, we show that mean reversion makes stocks less risky for investors with long investment horizons. Next, we consider a mean-variance efficient investor and show how mean reversion in stock prices affects such an investor's optimal portfolio weights. Finally, we discuss the implications of our findings for the investment decisions of long-term investors.
Keywords: 330; mean-variance efficiency; optimal portfolio weights; pension funds; risk-aversion; variance of stock returns